DAMPAK PENGEMBANGAN PANTAI JOKO TINGKIR DI KABUPATEN PEMALANG TERHADAP PENDAPATAN MASYARAKAT SEKITAR - Syaiful Amri, Muhammad; Karsinah, Karsinah (Penerbit Lafadz Jaya, 2025)
The development of coastal areas is one of the government's strategies in encouraging local economic growth through the tourism sector. Coastal areas that have various potential natural and cultural resources continue to be developed into leading tourist destinations in order to create jobs and increase local community income. This study aims to analyze the impact of attraction development, amenity development, accessibility development, and ancillary development on the income of the surrounding community. The research method used is descriptive quantitative with data collection techniques in the form of questionnaires distributed to people living around Joko Tingkir Beach, Pemalang Regency with data processing using the Ordinary Least Squares (OLS) model. The results showed that attraction development, amenity development, and accessibility development had a significant and positive effect on community income with a probability value of 0.0020, 0.0469, and 0.0162, respectively. Meanwhile, ancillary development has a probability of 0.1340, which means that ancillary development has a positive and insignificant effect on the income of the community around Joko Tingkir Beach.